Does State-Mandated Financial Education Reduce High School Graduation Rates? - Carly Urban (Institute of Labor Economics (IZA), 2022)
Concerned about low levels of financial literacy among teens and the importance of their looming financial decisions as emerging adults, state policymakers have expanded high school personal finance graduation requirements. Did these added requirements create an additional barrier for students? Comparing students in states with and without standalone personal finance course requirements before and after the requirements went into place, there is no evidence that these requirements reduced graduation rates overall, by race, by gender, or by family income. Existing research quantifies improvements in debt and credit behaviors, and these findings suggest there are not simultaneous adverse effects overall or for at-risk students.
Keywords: G53; D14; I24; 330; high school graduation; personal finance; financial education